Virtual reality cognitive remediation tool for individuals with mild cognitive impairment: study protocol for a feasibility randomized clinical trial - Perra, Alessandra; Primavera, Diego; Leonetti, Valerio; Montisci, Roberta; Carta, Daniele; Lorrai, Giulia; Locci, Aurora; Chessa, Luchino; Scuteri, Angelo; Cossu, Giulia; Nardi, Antonio Egidio; Valmaggia, Lucia; et al. (Frontiers in Public Health, 2024)
Introduction: With the growing elderly population, the European Union emphasizes the need to promote research in healthy aging trough multidisciplinary and innovative approaches, including the integration of advanced technologies like virtual reality (VR) in cognitive rehabilitation. Our study aims to present a protocol that will assess the feasibility and provide a preliminary measure of effectiveness for an intervention using immersive CR technology for cognitive remediation (CR) in individuals with Mild Cognitive Impairment (MCI). Methods: A feasibility randomized controlled clinical study will involve 30 individuals who are over 65 years old, both sex, who meet the diagnostic criteria for MCI from the University Hospital of Cagliari, randomly assigned to either the experimental condition or control group. Both groups will continue to receive standard pharmacological therapy. The experimental group will undergo a 3months cognitive remediation program using fully immersive VR with two sessions per week. Each session will last a maximum of sixty minutes and will be supervised by expert health professionals. In contrast, the control group will continue with standard care. The intervention program will be carried out by s psychiatric rehabilitation technicians and speech therapists, emphasizing a comprehensive framework aligned with healthcare needs. Feasibility will be assessed based on tolerability, including dropout rates and acceptability, which considers the proportion of recruited participants among those considered eligible and on side effects and level of satisfaction. The preliminary measures of effectiveness will be evaluated on quality of life, cognitive functions, biological and social rhythms, depressive symptoms and anxiety. Results: The trial findings will be submitted for publication in international peer-reviewed journals and shared at international meetings and conferences. Discussion: This study aiming to assess the feasibility and preliminary effectiveness of a fully immersive VR/CR program for MCI in order to give data for a subsequent confirmatory trial. The results are expected to significantly contribute to research on the prevention of neurocognitive degeneration, with a specific emphasis on enhancing the application of technologies. The strengths are the high technological innovation program for healthy ageing and multidisciplinary approach emphasizing a holistic framework aligned with health needs.